2023
DOI: 10.3389/fonc.2023.1074793
|View full text |Cite|
|
Sign up to set email alerts
|

Transarterial chemoembolization combined with lenvatinib versus transarterial chemoembolization combined with sorafenib for unresectable hepatocellular carcinoma: A systematic review and meta-analysis

Abstract: BackgroundThe combination of tyrosine kinase inhibitors (TKIs) and transarterial chemoembolization (TACE) fulfills an important role in the treatment of unresectable hepatocellular carcinoma (uHCC). Among the combination therapies, both lenvatinib and sorafenib combined with TACE are recommended as first-¬line treatments for uHCC. However, at present, limited data are available concerning the efficacy and safety of these two combination therapies in uHCC.MethodsA detailed systematic search for studies on lenva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Sorafenib showed a higher rate of HFSR (11 vs. 3%) and a lower rate of hypertension (14 vs. 23%) than lenvatinib. In our previous meta-analysis, there were significant differences regarding HFSR (HR, 0.51, 95%; CI, 0.27-0.95) and hypertension (HR, 3.05; 95% CI, 1.45-6.39) between the two combination therapy groups, and the differences in incidence of HFSR and hypertension were similar to results of the REFLECT trial (12,15). However, the present NMA found no significant difference regarding HFSR and hypertension between the two combination therapy groups.…”
Section: Discussionsupporting
confidence: 71%
“…Sorafenib showed a higher rate of HFSR (11 vs. 3%) and a lower rate of hypertension (14 vs. 23%) than lenvatinib. In our previous meta-analysis, there were significant differences regarding HFSR (HR, 0.51, 95%; CI, 0.27-0.95) and hypertension (HR, 3.05; 95% CI, 1.45-6.39) between the two combination therapy groups, and the differences in incidence of HFSR and hypertension were similar to results of the REFLECT trial (12,15). However, the present NMA found no significant difference regarding HFSR and hypertension between the two combination therapy groups.…”
Section: Discussionsupporting
confidence: 71%
“…This may also contribute to a more pronounced post-treatment fatigue, as patients may experience the biological effects of the drug over an extended period. When used in conjunction with gel, it effectively inhibits the development of new tumor blood vessels, achieving therapeutic efficacy[ 23 , 24 ]. Consequently, patients with larger tumor diameters may receive higher embolization doses, leading to transient liver and gallbladder ischemia, hepatomegaly, and peritoneal stimulation-induced pain.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. ( 70 ) conducted a meta-analysis comparing Lenv+TACE with Sora+TACE and found that the OS and PFS of the Lenv+TACE group were significantly better than those of Sora+TACE. In terms of safety, the incidence of hypertension and proteinuria was significantly higher in the Lenv+TACE group than in the Sora+TACE group, while the opposite was true for the hand-foot syndrome.…”
Section: Discussionmentioning
confidence: 99%